Application of the non-orthogonal laguerre-L2 basis to the calculation of electron-helium scattering at intermediate energy - Agus Kartono,; Mustafa Mamat, (Universiti Kebangsaan Malaysia, 2013)
Differential cross sections for excitation to the n=2 states of atomic helium by electrons were computed for incident energies in the range from 30 to 50 eV. The n=2 states excitation cross sections were calculated with the use of close-coupling expansion with a non-orthogonal Laguerre-L2 basis function. The present status of agreement between theory and experiment for excitation of the ground-state was quite satisfactory.